Pendekatan Manajemen Pesantren: Implementasi Team Assisted Individualization pada Program Ekstrakurikuler Bahasa Arab - Dian Zulfatul Iman; Muhammad Alfi Alfaridli; M. Fakhroni Hamzah (AL-BAYAN INSTITUTE, 2023)
This research explores the Team Assisted Individualization (TAI) model strategy in Arabic extracurricular programs at the Arabic Language Development Institute (LPBA) in Islamic boarding schools. This research aims to improve diverse and responsive learning approaches to increase the effectiveness of these extracurricular programs. Using a qualitative case study approach, data was collected through interviews, observation and document analysis, analyzed using data reduction, data presentation, restatement and drawing conclusions. These findings highlight the strategy of implementing TAI in the LPBA extracurricular program, which results in improved student learning outcomes and achievements. This approach effectively addresses the needs and potential of students, but needs to be adapted to more personal needs. This study contributes to the literature by providing insight into relevant educational practices in the context of Arabic language learning, emphasizing the importance of adapted teaching methods in increasing santri engagement and achievement in extracurricular programs at Islamic boarding schools